The protective effect of CALD identity in the presence of low income on missing teeth of Australian adults over time - Lisa Jamieson; Gloria Mejia; Dandara G Haag; Gustavo H Soares; Liana Luzzi; Xiangqun Ju (BMC Public Health, 2024)
Abstract Background ‘Culturally And Linguistically Diverse (CALD)’ populations have diverse languages, ethnic backgrounds, societal structures and religions. CALD populations have not experienced the same oral health benefits as non-CALD groups in Australia. However, the socio-demographic profile of Australian CALD populations is changing. This study examined how household income modifies the oral health of CALD and non-CALD adults in Australia. Methods Data were from two National Surveys of Adult Oral Health (NSAOH) conducted in 2004-06 (NSAOH 2004-06) and 2017-18 (NSAOH 2017-18). The outcome was self-reported number of missing teeth. CALD status was identified based on English not the primary language spoken at home and country of birth not being Australia. Social disadvantage was defined by total annual household income. Effect-measure modification was used to verify differences on effect sizes per strata of CALD status and household income. The presence of modification was indicated by Relative Excess Risk due to Interactions (RERIs). Results A total of 14,123 participants took part in NSAOH 2004-06. The proportion identifying as CALD was 11.7% and 56.7% were in the low-income group, and the mean number of missing teeth was 6.9. A total of 15,731 participants took part in NSAOH 2017-18. The proportion identifying as CALD was 18.5% and 38.0% were in the low-income group, and the mean number of missing teeth was 6.2. In multivariable modelling, the mean ratio (MR) for CALD participants with low household income in 2004-06 was 2% lower than the MR among non-CALD participants with high household income, with the RERI being − 0.23. Non-CALD participants from lower income households had a higher risk of having a higher number of missing teeth than low income CALD individuals (MR = 1.66, 95%CI 1.57–1.74 vs. MR = 1.43 95%CI 1.34–1.52, respectively). In 2017-18, the MR for CALD participants with low household income was 3% lower than the MR among non-CALD participants with high household income, with the RERI being − 0.11. Low income CALD participants had a lower risk of missing teeth compared to their non-CALD counterparts (MR = 1.43, 95% CI 1.34–1.52 vs. MR = 1.57, 95% CI 1.50–1.64). Conclusions The negative RERI values indicate that the effect-measure modification operates in a negative direction, that is, there is a protective element to being CALD among low income groups with respect to mean number of missing teeth.